Effect of monetary and non-monetary incentives in 3 different fields - (:unkn) unknown (Università della Calabria, 2022)
This thesis aims to investigate the effects of monetary and non-monetary incentives in 3 different fields. In the first chapter, we analyse whether the behavioural theory of Student Identity Priming has positive effects on student performance. By conducting an experiment on both students and former students - taken as a control trial - we observe that stimulating students' identity through motivational pictures and videos has positive effects on academic performance. The second chapter aims to analyse whether an increase in women's employment through government incentives has led to a reduction in gender-based violence. The results show that greater socio-economic independence leads to a reduction in gender-based violence. Finally, the third chapter examines the effect of regional incentives provided for cutting the waste tax on tax evasion. Analysing data from the municipal budgets of two Italian regions, we find that the tax cut, reduced by incentives, leads to a reduction in tax evasion. To support this, we analyse other taxes that are not cut in the same way.
Dottorato di Ricerca in Scienze Economiche e Aziendali. Ciclo XXXIV
Keywords: Incentives; Priming; Tax Compliance; Gender-based Violence; Theory of Incentives